Application of the Li-Pro-GP learning model to improve students’ conceptual understanding and creativity - Yuni Pantiwati; Permana, Fendy Hardian; Kusniarti, Tuti; Sari, Tasya Novian Indah; Nurrohman, Endrik (Universitas Negeri Jakarta, 2022)
Concept understanding and product creativity of Ma'arif class VII A junior high school students are less than optimal. This problem is because learning activities do not invite students to increase literacy. Based on this, it is necessary to innovate learning. The purpose of this research is to apply Li-Pro-GP learning (Project-Based Science Literacy in the integrated scientific literacy movement strengthening character education) to improve conceptual understanding and creativity of learning poster products. The type of research used is quasi-experimental research (quasi-experimental) using a one-group pretest-posttest design. The research population is seventh-grade junior high school students. While sampling using purposive sampling. The research sample is all Ma'arif junior high school students in class VII A. Data collection techniques use tests and documentation with research instruments, namely written test questions in the form of essays used to pretest and posttest. The measurement of the creativity of the learning poster product uses the product creativity rubric. Data analysis using paired t-test with the help of data processing applications IBM SPSS 26 and Ms.Excel. The results showed that: 1) there was an effect of using the Li-Pro-GP learning model on the ability to understand concepts; 2) there is an effect of using the Li-Pro-GP learning model on the creativity of the learning poster product.